2008
DOI: 10.1073/pnas.0806979105
|View full text |Cite
|
Sign up to set email alerts
|

Transmitter-receptor mismatch in GABAergic synapses in the absence of activity

Abstract: Competition among different axons to reach the somatodendritic region of the target neuron is an important event during development to achieve the final architecture typical of the mature brain. Trasmitter-receptor matching is a critical step for the signaling between neurons. In the cerebellar cortex, there is a persistent competition between the two glutamatergic inputs, the parallel fibers and the climbing fibers, for the innervation of the Purkinje cells. The activity of the latter input is necessary to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
8
1
Order By: Relevance
“…7D,E,G ). Recently, it has been shown that following blockage of electrical activity, GluRδ2 is expressed not only on spines but also in excitatory postsynaptic assemblies in the smooth surface of PC proximal dendrites [35]. In our experiments, we failed to observe GluRδ2 signals in the deeper section of the granular layer.…”
Section: Resultscontrasting
confidence: 70%
“…7D,E,G ). Recently, it has been shown that following blockage of electrical activity, GluRδ2 is expressed not only on spines but also in excitatory postsynaptic assemblies in the smooth surface of PC proximal dendrites [35]. In our experiments, we failed to observe GluRδ2 signals in the deeper section of the granular layer.…”
Section: Resultscontrasting
confidence: 70%
“…Activity ensures formation of functional synapses, and the level of activity determines the class of synapse. This process seems to involve the action of diffusible factors that may include the transmitters as well as other components, such as trophic factors 5457 . The results are consistent with the demonstration of glutamatergic synapses by classically cholinergic neonatal mouse motor neurons 24,25 .…”
Section: Activity-dependent Transmitter–receptor Matchingmentioning
confidence: 99%
“…Transmitter receptor matching occurs in parallel with activity-dependent transmitter respecification (Borodinsky and Spitzer, 2007; Cesa et al, 2008; Dulcis and Spitzer, 2008). Transmitter and receptor respecification can be triggered by experimental manipulations or by natural sensory stimuli that selectively activate a neuronal circuit (Trudeau and Gutierrez, 2007; Dulcis and Spitzer, 2008).…”
Section: Introductionmentioning
confidence: 99%